2015
DOI: 10.17475/kuofd.94670
|View full text |Cite
|
Sign up to set email alerts
|

Cortinarius caperatus (Pers.) Fr., A New Record For Turkish Mycobita

Abstract: In this study, Cortinarius caperatus (Pers.) Fr. belonging to the family Cortinariaceae was recorded for the first time from Turkey. A short description, ecology, distribution and photographs related to macro and micromorphologies of the species are provided and discussed briefly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Worldwide, the genus Cortinarius is represented by more than 5000 records (Kirk, 2011). Approximate100 records of this genus have been reported from our country and more records are being added gradually with the support of molecular data (Sesli and Denchev, 2014;Akata et al, 2015;Sesli et al, 2015;Sesli et al, 2016;Sesli and Liimatainen, 2018;Sesli, 2018;Kalmer et al, 2019) Cortinarius rufo-olivaceus has been previously reported in Turkey from Osmaniye province (Isıloglu and Öder, 1995). However, no morphological or molecular data have been provided for this species.…”
Section: Introductionsupporting
confidence: 53%
“…Worldwide, the genus Cortinarius is represented by more than 5000 records (Kirk, 2011). Approximate100 records of this genus have been reported from our country and more records are being added gradually with the support of molecular data (Sesli and Denchev, 2014;Akata et al, 2015;Sesli et al, 2015;Sesli et al, 2016;Sesli and Liimatainen, 2018;Sesli, 2018;Kalmer et al, 2019) Cortinarius rufo-olivaceus has been previously reported in Turkey from Osmaniye province (Isıloglu and Öder, 1995). However, no morphological or molecular data have been provided for this species.…”
Section: Introductionsupporting
confidence: 53%
“…Numerous studies have been carried out on Turkish macromycota and some of them are still in progress Akata and Uzun, 2017;Akata et al, 2015a,b, Alkan et al, 2016Allı et al, 2017;Altuntaş et al, 2017;Demirel et al, 2016;Doğan and Kurt, 2016;Öztürk et al, 2017;Sesli and Denchev, 2008;Sesli et al, 2016). According to the present literature, some investigations on macrofungal taxonomy around the research area were carried out by , , Karamanoğlu and Öder (1973), Öztürk et al (1990), Solak andGücin, 1992;Stojchev et al (1998).…”
Section: Figure 1 Map Of the Research Areamentioning
confidence: 99%
“…The aim of the present study is to contribute to Turkish Mycota by introducing two Cortinarius species collected from Trabzon. Many Cortinarius species had ben presented from different regions of Turkey (Türkekul, 2003;Kaya et al, 2009;Kaşık et al, 2011;Uzun et al, 2013;Akata et al, 2015;Doğan and Kurt, 2016;Sesli and Liimatainen, 2018) but C. atroalbus and C. duracinobtusus haven't been reported before.…”
Section: Introductionmentioning
confidence: 99%